Incidence and risk factor analysis of moderate-to-severe pain after preoperative CT-guided hook-wire puncture localization of pulmonary nodules - Jiajian Pan; Tianci Feng; Jiayi Wang; Ran Ma; Tianyue Ma; Yong Ge; Teng Sun; Shoujie Feng; Cheng Zhang; Hao Zhang (BMC Surgery)
Abstract Background Pain is a relatively common complication after hook-wire puncture localization. However, the problem of pain occurrence following this localization procedure has not been sufficiently examined. In this prospective study, we aimed to investigate the incidence and risk factors associated with acute pain after preoperative CT-guided hook-wire puncture localization of pulmonary nodules. Methods Clinical data were collected prospectively from patients with small pulmonary nodules who underwent preoperative CT-guided hook-wire puncture localization between May 2022 and May 2023 at the Affiliated Hospital of Xuzhou Medical University. Patients were divided into two groups on the basis of the presence or absence of moderate-to-severe pain following the localization process. Univariate logistic analysis was conducted to analyse the clinical data of the two groups. Subsequently, the significant variables (P < 0.1) from the univariate analysis were subjected to multivariate logistic analysis, followed by the establishment of regression equations to determine the significant risk factors related to moderate-to-severe pain after hook-wire puncture localization. Results A total of 281 patients with small pulmonary nodules undergoing preoperative CT-guided hook-wire puncture localization were finally included, with a mean age of 54.86 years (SD = 12.1 years) and female predominance (67.6%). In the resting state, 53% of the patients reported moderate-to-severe pain. Univariate analysis revealed that age (P = 0.085), the depth of localization needle insertion into the lung (P = 0.024) and the location of the chest wall puncture (P = 0.07) were associated with moderate-to-severe pain occurrence after hook-wire puncture localization (P < 0.1). Furthermore, multivariate logistic regression analysis demonstrated that the depth of localization needle insertion into the lung (OR = 0.953, 95% CI: 0.914–0.992, P = 0.02) and the location of the chest wall puncture (lateral chest wall vs. anterior chest wall: OR = 2.101, 95% CI: 1.166–3.784, P = 0.013; posterior chest wall vs. anterior chest wall: OR = 1.163, 95% CI: 0.895–2.971, P = 0.11) were independent predictors of moderate-to-severe pain incidence following CT-guided hook-wire puncture localization (P < 0.05). Conclusion Moderate-to-severe pain is prevalent in patients with pulmonary nodules who undergo preoperative CT-guided hook-wire puncture localization. The depth of needle insertion into the lung and the location of the chest wall puncture are significant predictors of moderate-to-severe pain onset.